Mitochondrial ROS, ER Stress, and Nrf2 Crosstalk in the Regulation of Mitochondrial Apoptosis Induced by Arsenite - Orazio Cantoni; Ester Zito; Andrea Guidarelli; Mara Fiorani; Pietro Ghezzi (MDPI AG, 2022)
Long-term ingestion of arsenicals, a heterogeneous group of toxic compounds, has been associated with a wide spectrum of human pathologies, which include various malignancies. Although their mechanism of toxicity remains largely unknown, it is generally believed that arsenicals mainly produce their effects via direct binding to protein thiols and ROS formation in different subcellular compartments. The generality of these mechanisms most probably accounts for the different effects mediated by different forms of the metalloid in a variety of cells and tissues. In order to learn more about the molecular mechanisms of cyto- and genotoxicity, there is a need to focus on specific arsenic compounds under tightly controlled conditions. This review focuses on the mechanisms regulating the mitochondrial formation of ROS after exposure to low concentrations of a specific arsenic compound, NaAsO2, and their crosstalk with the nuclear factor (erythroid-2 related) factor 2 antioxidant signaling and the endoplasmic reticulum stress response.